PENGENALAN OLAH NASAF, SUARA, DAN SUKMA BAGI SISWA SMP KABUPATEN KUNINGAN - Kautsar, Tifani; Hidayat, Arip; Andriyana, Andriyana (Pusat Pengembangan dan Kajian Sarana dan Prasarana Pendidikan (P2K Sarprasdik), 2023)
Abstract:Teaching literature on drama material is needed by students to hone creativity and critical thinking skills in a drama performance. Drama as a literary work and a performance work are two important things to be taught in schools. Devotion to teaching drama to students is necessary to build a construct of a steady understanding of play. Community service with the PRA (Participatory Rural Appraisal) method which involves everyone and all participants actively participate in the service process. The midwifery process conducts direct practice on the material provided and conducts joint evaluations. The results of the evaluation produce practical material for the introduction of basic theater exercises proven to hone creative thinking.Abstrak: Pengajaran sastra pada materi drama sangat dibutuhkan siswa untuk mengasah kreatifitas dan kemampuan berfikir kritis dalam sebuah pementasan drama. Drama sebagai karya sastra dan karya pentas merupakan dua hal yang penting untuk diajarkan disekolah. Pengabdian tentang pengajaran drama bagi siswa diperlukan untuk membangun konstruk pemahaman yang ajeg tentang permainan drama. Pengabdian dengan metode PRA (Participatory Rural Appraisal) yang melibatkan semua orang dan semua partisipan ikut aktif dalam proses pengabdian. Proses pengabidian melakukan praktik langsung terhadap materi yang diberikan dan melakukan evaluasi bersama. Hasil evaluasi menghasilkan materi praktik pengenalan latihan dasar teater terbukti dapat mengasah berfikir kreatif.